2014
DOI: 10.4103/0971-6203.125509
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of diagnostic reference levels in computed tomography for select procedures in Pudhuchery, India

Abstract: Computed tomography (CT) scanner under operating conditions has become a major source of human exposure to diagnostic X-rays. In this context, weighed CT dose index (CTDIw), volumetric CT dose index (CTDIv), and dose length product (DLP) are important parameter to assess procedures in CT imaging as surrogate dose quantities for patient dose optimization. The current work aims to estimate the existing dose level of CT scanner for head, chest, and abdomen procedures in Pudhuchery in south India and establish dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
1
15
1
Order By: Relevance
“…Also, from Tables 5 and 6 it is found that the percentage difference between the fabricated and console CTDI v and standard and console CTDI v are well within the limits recommended by Atomic Energy Regulatory Board (AERB) which is based on International Commission on Radiological Protection (ICRP) standards. [ 18 19 20 ] The large differences for lower kVs may be due to the dose evaluation/calibration method employed by the manufacturer.…”
Section: Resultsmentioning
confidence: 99%
“…Also, from Tables 5 and 6 it is found that the percentage difference between the fabricated and console CTDI v and standard and console CTDI v are well within the limits recommended by Atomic Energy Regulatory Board (AERB) which is based on International Commission on Radiological Protection (ICRP) standards. [ 18 19 20 ] The large differences for lower kVs may be due to the dose evaluation/calibration method employed by the manufacturer.…”
Section: Resultsmentioning
confidence: 99%
“…One of these values to be calculated was the estimated length (L) measured in centimeter (cm) which was based on the CTDI vol and DLP generated by the CT scanner according to the following equation (Ekpo et. al., 2018) (Saravanakumar et. al., 2014).…”
Section: Table (1): Ct Examination Parameters From Azadi Hospitalmentioning
confidence: 99%
“…Even though there is enough recently published regional CT radiation dose data from south India,[ 15 16 17 18 ] any such data have not considered the make of CT equipment (number of slices of CT) and actual number of phases in contrast CT examinations. These factors are important with regard to actual dose delivered to the patient.…”
Section: Introductionmentioning
confidence: 99%